Wirtschaftlichkeitsberechnung für MBT: Wann sich modellbasiertes Testen lohnt - Faragó, David; Törsel, Arne-Michael; Mlynarski, Michael; Weißleder, Stephan; Güldali, Baris; Brandes, Christian (OBJEKTspektrum)
Modellbasiertes Testen verspricht potenziell eine höhere Effizienz und Effektivität im Testprozess. Ob im eigenen Kontext der Einsatz wirtschaftlich ist, ist jedoch häufig unklar. Dieser Beitrag analysiert systematisch Kosten- und Nutzenfaktoren und stellt ein Verfahren zur Abschätzung der Wirtschaftlichkeit des modellbasierten Testens vor. Anhand eines Beispiels wird der Ablauf veranschaulicht.

Spin injection, transport, and relaxation in spin light-emitting diodes: magnetic field effects - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (Spintronics VI)

Spin relaxation length in quantum dot spin LEDs - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (physica status solidi (c))

Influence of recombination center interaction on the photoluminescence of AlGaAs/GaAs heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Hanle effect in (In,Ga)As quantum dots: Role of nuclear spin fluctuations - Kuznetsova, M. S.; Flisinski, K.; Gerlovin, I. Ya.; Ignatiev, I. V.; Kavokin, K. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Origins of conductance anomalies in ap-type GaAs quantum point contact - Komijani, Y.; Csontos, M.; Ihn, T.; Ensslin, K.; Meir, Y.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Grazing-incidence X-ray diffraction of single GaAs nanowires at locations defined by focused ion beams - Bussone, Genziana; Schott, Rüdiger; Biermanns, Andreas; Davydok, Anton; Reuter, Dirk; Carbone, Gerardina; Schülli, Tobias U.; Wieck, Andreas D.; Pietsch, Ullrich (Journal of Applied Crystallography)

Influence of surface states on quantum and transport lifetimes in high-quality undoped heterostructures - Wang, D. Q.; Chen, J. C. H.; Klochan, O.; Das Gupta, K.; Reuter, Dirk; Wieck, A. D.; Ritchie, D. A.; Hamilton, A. R. (Physical Review B)

Scaling of the Kondo zero-bias peak in a hole quantum dot at finite temperatures - Klochan, O.; Micolich, A. P.; Hamilton, A. R.; Reuter, Dirk; Wieck, A. D.; Reininghaus, F.; Pletyukhov, M.; Schoeller, H. (Physical Review B)

Hot carrier effects on the magneto-optical detection of electron spins in GaAs - Henn, T.; Heckel, A.; Beck, M.; Kiessling, T.; Ossau, W.; Molenkamp, L. W.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Many-body correlations of electrostatically trapped dipolar excitons - Schinner, G. J.; Repp, J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O.; Holleitner, A. W.; Kotthaus, J. P. (Physical Review B)

Optical Spectroscopy of Spin Noise - Zapasskii, V. S.; Greilich, A.; Crooker, S. A.; Li, Yan; Kozlov, G. G.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

Confinement and Interaction of Single Indirect Excitons in a Voltage-Controlled Trap Formed Inside Double InGaAs Quantum Wells - Schinner, G. J.; Repp, J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O.; Holleitner, A. W.; Kotthaus, J. P. (Physical Review Letters)

Temperature dependence of hole spin coherence in (In,Ga)As quantum dots measured by mode-locking and echo techniques - Varwig, S.; René, A.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Aharonov–Bohm rings with strong spin–orbit interaction: the role of sample-specific properties - Nichele, F; Komijani, Y; Hennel, S; Gerl, C; Wegscheider, W; Reuter, Dirk; Wieck, A D; Ihn, T; Ensslin, K (New Journal of Physics)

On the annealing mechanism of AuGe/Ni/Au ohmic contacts to a two-dimensional electron gas in GaAs/AlxGa1−xAs heterostructures - Koop, E J; Iqbal, M J; Limbach, F; Boute, M; van Wees, B J; Reuter, Dirk; Wieck, A D; Kooi, B J; van der Wal, C H (Semiconductor Science and Technology)

Correlation and dephasing effects on the non-radiative coherence between bright excitons in an InAs QD ensemble measured with 2D spectroscopy - Moody, G.; Singh, R.; Li, H.; Akimov, I.A.; Bayer, M.; Reuter, Dirk; Wieck, A.D.; Cundiff, S.T. (Solid State Communications)

Anisotropic Zeeman shift in p-type GaAs quantum point contacts - Komijani, Y.; Csontos, M.; Shorubalko, I.; Zülicke, U.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (EPL (Europhysics Letters))

Fifth-order nonlinear optical response of excitonic states in an InAs quantum dot ensemble measured with two-dimensional spectroscopy - Moody, G.; Singh, R.; Li, H.; Akimov, I. A.; Bayer, M.; Reuter, Dirk; Wieck, A. D.; Cundiff, S. T. (Physical Review B)

Confinement Effects on Biexciton Binding in Semiconductor Quantum Dots Measured with 2D Coherent Spectroscopy - Moody, G.; Singh, R.; Li, H.; Akimov, I. A.; Bayer, M.; Reuter, Dirk; Wieck, A. D.; Bracker, A. S.; Gammon, D.; Cundiff, S. T. (CLEO: 2013)

Observation of the Kondo effect in a spin-3/2 hole quantum dot - Klochan, O.; Micolich, A.P.; Hamilton, A.R.; Trunov, K.; Reuter, Dirk; Wieck, A.D. (COMMAD 2012)

Excitons, Biexcitons, and Trions in an InAs Quantum Dot Ensemble Studied with 2D Fourier-Transform Spectroscopy - Moody, Galan; Singh, Rohan; Li, Hebin; Akimov, Ilya; Bayer, Manfred; Reuter, Dirk; Wieck, Andreas; Cundiff, Steven T. (Conference on Lasers and Electro-Optics 2012)

Coherence of Fine-Structure States of an InAs Quantum Dot Ensemble Studied with 2D Fourier-Transform Spectroscopy - Singh, R.; Moody, G.; Li, H.; Akimov, I. A.; Bayer, M.; Reuter, Dirk; Wieck, A. D.; Cundiff, S. T. (Conference on Lasers and Electro-Optics 2012)

Counting statistics of hole transfer in ap-type GaAs quantum dot with dense excitation spectrum - Komijani, Y.; Choi, T.; Nichele, F.; Ensslin, K.; Ihn, T.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Spin relaxation in spin light-emitting diodes: effects of magnetic field and temperature - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (Ultrafast Phenomena and Nanophotonics XVII)

Primacy versus Recency Effects in Extended Service Encounters - Garnefeld, Ina; Steinhoff, Lena (Journal of Service Management)

Umsatz- und Profitabilitätsauswirkungen industrieller Dienstleistungen – Eine latente Wachstumskurvenanalyse

Paradigmen in der Curriculumtheorie: Das Lernfeldkonzept im Kontext der Input-Output-Diskussion - Kremer, H.-Hugo (Vielfalt an Übergängen in der beruflichen Bildung - zwölf Ansichten)

Structural enhancement of ZnO on SiO2 for photonic applications - Ruth, Marcel; Meier, Cedrik (AIP Advances)

Object-oriented Modeling of Multimedia Applications - Engels, Gregor; Sauer, Stefan (Handbook of Software Engineering and Knowledge Engineering)

Quality Assurance with Dynamic Meta Modeling - Soltenborn, Christian
Dynamic Meta Modeling (DMM) is a semantics specification technique targeted at MOF-based modeling languages, where a language's behavior is defined by means of graphical operational rules which change runtime models. The DMM approach has first been suggested by Engels et al. in 2000; Hausmann has then defined the DMM language on a conceptual level within his PhD thesis in 2006. Consequently, the next step was to bring the existing DMM concepts alive, and then to apply them to different modeling languages, making use of the lessons learned to improve the DMM concepts as well as the DMM tooling. The result of this process is the DMM++ method, which is presented within this thesis. Our contributions are three-fold: First, and according to our experiences with the DMM language, we have introduced new concepts such as refinement by means of rule overriding, and we have strengthened existing concepts such as the dealing with universally quantified structures or attributes. Second, we have developed a test-driven process for semantics specification: A set of test models is created, and their expected behavior is fixed. Then, the DMM rules are created incrementally, finally resulting in a DMM ruleset realizing at least the expected behavior of the test models. Additionally, we have defined a set of coverage criteria for DMM rulesets which allow to measure the quality of a set of test models. Third, we have shown how functional as well as non-functional requirements can be formulated against models and their DMM specifications. The former is achieved by providing a visual language for formulating temporal logic properties, which are then verified with model checking techniques, and by allowing for visual debugging of models failing a requirement. For the latter, the modeler can add performance information to models and analyze their performance properties, e.g. average throughput.

Business Process Models - Change Management - Gerth, Christian
Driven by the need for a closer alignment of business and IT requirements, the role of business process models in the development of enterprise software systems has increased continuously. Similar to other software artifacts, process models are developed and refined in team environments by several stakeholders, resulting in different versions. These versions need to be merged in order to obtain an integrated process model. Existing solutions to this basic problem in the field of software configuration management are mainly limited to textual documents, e.g., source code. This monograph presents a generally applicable framework for process model change management, which provides easy-to-use comparison and merging capabilities for the integration of different process model versions. The framework supports popular modeling languages such as BPMN, BPEL, or UML Activity Diagrams. Differences between process models are represented in terms of intuitive, high-level change operations. Equipped with a sophisticated analysis of dependencies and a semantic-aware computation of conflicts between differences, the framework constitutes a comprehensive and practically usable solution for process model change management in the model-driven development of enterprise software systems.

How backhaul networks influence the feasibility of coordinated multipoint in cellular networks - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Kellerer, Wolfgang; Karl, Holger (IEEE Communications Magazine)

Ein pragmatischer Ansatz zur Entwicklung situationsgerechter Entwicklungsmethoden - Spijkerman, Michael (Software Engineering 2013 - Workshopband (inkl. Doktorandensymposium) SE 2013 (to appear))

Kaos4SOA - Extending KAOS Models with Temporal and Logical Dependencies - Nagel , Benjamin; Gerth , Christian; Post, Jennifer; Engels, Gregor (Proceedings of the CAiSE'13 Forum at the 25th International Conference on Advanced Information Systems Engineering (CAiSE'13))

CVSM 2013 Challenge: Recognizing High-level Edit Operations in Evolving Models. - Kehrer , Timo; Gerth, Christian (Proceedings of the Workshop on Comparison and Versioning of Software Models (CVSM'13))

Wiederverwendbarkeit von Migrationswissen durch Techniken der modellgetriebenen Softwareentwicklung - Grieger , Marvin; Sauer, Stefan (Software Engineering 2013 Workshopband)

Goal-driven Composition of Business Process Models - Nagel , Benjamin; Gerth , Christian; Engels, Gregor (Proceedings of the 9th Workshop on Engineering Service-Oriented Applications (WESOA 2013) (accepted for application))

Assembly-based Method Engineering with Method Patterns - Fazal-Baqaie , Masud; Luckey , Markus; Engels, Gregor (Software Engineering 2013 Workshopband)

Instrumentenentwicklung zur Messung von Lernstrategien in mathematikhaltigen Studiengängen - Göller, Robin; Kortemeyer, Jörg; Liebendörfer, Michael; Biehler, Rolf; Hochmuth, Reinhard; Krämer, Jana; Ostsieker, Laura; Schreiber, Stephan (Beiträge zum Mathematikunterricht 2013: Vorträge auf der 47. Tagung für Didaktik der Mathematik)

Mathe – nein danke? Interesse im und am Mathematikstudium bei Grundschullehramtsstudierenden mit Pflichtfach - Kolter, Jana; Liebendörfer, Michael (Mathematik im Übergang Schule / Hochschule und im ersten Studienjahr)

Interest and Self-Determination in the Transition to Studying Mathematics - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the 37th Conference of the International Group for the Psychology of Mathematics Education)

Interest in Mathematics and the First Steps at the University - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the 8th Conference of European Research in Mathematics Education)

Surface Diffusion of 3d-Metals on W(110) - Reuter, Dirk; Gerth, Gerhard; Kirschner, J. (Surface Diffusion)

Werte als Ausgangsbasis der Berufsorientierung in Justizvollzugsanstalten - Beutner, Marc; Rohde, S (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung. Konzepte zur beruflichen Bildung im Jungtätervollzug)

Ausbildungsfähigkeit und Basiskompetenzen – Eine Herausforderung für den Justizvollzug - Beutner, Marc; Rose, S (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung. Konzepte zur beruflichen Bildung im Jungtätervollzug)

Middeke,M. / Schnierer, P.P. / Sierz, A. (Hg.): The Methuen Guide to Contemporary British Playwrights - Tönnies, Merle (Anglia)

Rossow, H. Globalismus und Lew Labour - Tönnies, Merle (Anglistik. International Journal of English Studies)

Baumbach, S. / Neumann, B. / Nünning, A.: A History of British Drama - Tönnies, Merle (Anglistik. International Journal of English Studies)

COR-VET – Career Orientation in Vocational Education and Training in Europe - Beutner, Marc; Fortmann, L. M. (Kölner Zeitschrift für Wirtschaft und Pädagogik)